Koncepcje responsywności jako odpowiedź na postulaty „uwrażliwienia” demokracji przedstawicielskiej - Abramowicz, Bartosz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
The author discusses two concepts of responsiveness in his paper: the concept of active society, developed by Amitai Etzioni, and the concept of responsive public administration by Mateusz Stêpieñ. The author finds both concepts potentially inspiring in the context of theoretical proposals to overcome some dysfunctions of representative democracy. The author of the paper also proposes to include the concepts of responsiveness in the framework of the so-called transformation trend of theories of democracy, which perceives politics as the transformation of individual preferences through rational discussion. The author observes a certain convergence between the concepts of responsiveness and the main assumptions of deliberative democracy (falling into the above transformation paradigm). Both concepts attempt at finding a ‘golden mean’ between liberal and republican visions of state community, while significantly ‘supplementing’ liberal democracy concepts, especially those where politics is reduced to a process of an auction of interests. Etzioni’s concept is more philosophically oriented and can serve as a theoretical foundation for more general considerations on the functioning of a democratic system and the relations between authorities and citizens. A more practically oriented concept of responsive administration can inspire the analyses of a desired model of self-government administration, whose role in the context of relations with the citizens of local communities is sometimes equal to that of local authorities.
The concepts of responsiveness as a reaction to the postulates to make representative democracy more ‘sensitive’